Effects of Dietary Regimens and Brown-Egg Pullet Strain on Growth and Development - Anderson, K.E. (International Journal of Poultry Science, 2010)
This study consisted of; two strains of brown-egg pullets, the Hy-Line (HB) and H&N (BN) Brown were raised on three different dietary regimens resulting in a 2 x 3 factorial design. The three different regimens were a standard Step-down Protein Regimen (SDP) comprised of a 20% CP Starter, 0-6 week, 18% CP Grower 1, 7-12 week and 16% CP Grower 2, 13-18 week; a Step-up Protein Regimen (SUP9) comprised of a 12% CP Starter, 0-9 week, 16% CP Grower 2, 10-16 week and 18% CP Grower 1, 17-18 week and a Step-up Protein Regimen (SUP12) comprised of a 12% CP Starter, 0-12 week, 16% CP Grower 2, 13-16 week and 18% CP Grower 1, 17-18 week. The pullets were housed in an environmentally controlled rearing facility with trideck battery cages. Feed consumption and body weights were measured bi-weekly and mortality was recorded daily. At 17 week of age a sample of 20 pullets from each strain and regimen combination were randomly selected and brought to the laboratory for body composition analysis. At 18 week the HB and BN strains only differed in livability with the HB having a 4.2% greater (p<0.05) liveability than the BN pullets. There was a stepwise reduction (p<0.05) in total protein intake from the SDP, SUP9 and SUP12, however, energy, Ca, P and lysine consumption were comparable. The SUP9 and SUP12 feeding regimens resulted in significantly (p<0.05) lower BW than the SDP regimen pullets. The SUP12 regimen significantly reduced sternum length below that obtained with the SDP or SUP9 program 11.0 vs. 11.2 and 11.3 cm, respectively. Tibial breaking strength was no different between the strains or regimens. This study shows that pullets reared on SUP regimens would have lower body weights with few differences in body composition percentages. Indicating that reduced dietary protein and energy would result in smaller pullets with comparable body composition.